1) -1 + [tex]\frac{a}{2}[/tex] dla a = -2
-1 + [tex]\frac{-2}{2}[/tex] = -1 + (-1) = -2
4 - a dla a = -2
4 - (-2) = 4 +2 = 6
[tex]\frac{2}{3}[/tex](a - 1) dla a = -2
[tex]\frac{2}{3}[/tex]a - [tex]\frac{2}{3}[/tex] = [tex]\frac{2}{3}[/tex] x -2 - [tex]\frac{2}{3}[/tex] = -[tex]\frac{4}{3}[/tex] - [tex]\frac{2}{3}[/tex] = -[tex]\frac{6}{3}[/tex] = -2
2a + 2 dla a = -2
2 x -2 + 2 = -4 + 2 = -2
PRAWDA
2) -1 + [tex]\frac{a}{2}[/tex] dla a = 1
-1 + [tex]\frac{1}{2}[/tex] = -[tex]\frac{1}{2}[/tex] -[tex]\frac{1}{2}[/tex] < 0
4 - a dla a = 1
4 - 1 = 3 3 > 0
[tex]\frac{2}{3}[/tex](a - 1) dla a = 1
[tex]\frac{2}{3}[/tex]a - [tex]\frac{2}{3}[/tex] = [tex]\frac{2}{3}[/tex] - [tex]\frac{2}{3}[/tex] = 0 (niedodatnie)
2a + 2 dla a = 1
2 + 2 = 4 4 > 0
FAŁSZ